New Therapies to Modulate Post-Infarction Inflammatory Alterations in the Myocardium: State of the Art and Forthcoming Applications - Clerc, Olivier F.; Haaf, Philip; Buechel, Ronny R; Gaemperli, Oliver; Zellweger, Michael J. (Current Radiopharmaceuticals, 2021)
Acute myocardial infarction (AMI) is a major cause of morbidity and mortality worldwide. AMI causes necrosis of cardiac cells and triggers a complex inflammatory response, affecting infarct size, cardiac function and clinical outcomes. This inflammatory response can be divided into 3 phases: 1) the pro-inflammatory phase, in which the release of damage-associated molecular patterns from necrotic cells triggers the secretion of pro-inflammatory mediators and attracts immune cells to clean the debris, further damaging viable myocardium, 2) the reparative phase, in which anti-inflammatory signals activate immune-modulating cells and trigger the production of a stable scar, 3) the maturation phase, in which inflammatory and fibrotic signals are suppressed, but may persist, leading to left ventricular adverse remodelling. Thus, the inflammatory response is an appealing therapeutic target to improve the outcomes of patients with AMI. Numerous anti-inflammatory therapies have shown potential in animal models, but the translation to human trials exhibited limited benefit. Glucocorticoids and non-steroidal anti-inflammatory drugs showed signals of harm due to their non-specific effects. Other broad inhibitors, e.g., methotrexate, cyclosporine, or colchicine, did not improve clinical outcomes as acute therapies for MI. Specific inhibitors of the complement cascade, adhesion molecules, or inflammatory mediators were mostly disappointing in humans. However, an interleukin-1 inhibitor (anakinra) and a matrix metalloproteinase inhibitor (doxycycline) improved clinical outcomes in patients with AMI. Promising RNAse1, anti-toll-like receptor 2 antibodies, and inflammasome inhibitors still need to be tested in humans. Finally, positive results should be replicated in large clinical trials before they can be implemented into the standard AMI therapy.
Keywords: repair